GAME EDUKATIF BERBASIS CONSTRUCT 3 SEBAGAI MEDIA PEMBELA-JARAN INTERAKTIF UNTUK ANAK USIA DINI DI RA-ALFARISI - Rusmanto, Ayu Hafidzah; Zaliluddin, Dadan; Bastian , Ade (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2025)
The advancement of multimedia technology has fostered the emergence of interactive learning media that can enhance students’ interest and comprehension, particularly for early childhood education. This study aims to develop an educational Game using Construct 3 as an interactive learning medium at RA Al-Farisi. The development process applied the Single Development Life Cycle (SDLC) with a Rapid Prototyping approach, which included needs analysis, design, prototyping, testing, and evaluation. The Game content integrates basic educational materials such as the introduction of animals, the solar system, family members, communication tools, and religious values. The usability testing involved teachers and students of RA Al-Farisi using the System Usability Scale (SUS) instrument. The results indicate that the developed educational Game demonstrates good usability, is easy to understand, and engaging for young learners. Therefore, this Game is effective as an alternative interactive learning medium that stimulates children’s cognitive and motor development while enhancing their learning motivation.